Morphological and molecular characterization of Coynema poeyi (Coy, García & Álvarez, 1993) (Oxyuridomorpha: Hystrignathidae) from Antillanax pertyi (Kaup, 1869) (Coleoptera: Passalidae) from Cuba and new locality records for the species - Morffe, Jans; García, Nayla; Breugelmans, Karin; Adams, Byron J.; Hasegawa, Koichi (Zootaxa, 2018)
Coynema poeyi (Coy, García & Álvarez, 1993) (Oxyuridomorpha: Hystrignathidae) is redescribed and illustrated with the aid of SEM. New features of the cephalic end of both sexes and copulatory papillae pattern of the males were observed and the generic diagnosis is emended in order to include such features. New locality records are given. The phylogenetic position of the species is inferred on the basis of the D2-D3 segment of the LSU rDNA. C. poeyi is located basal in a monophyletic clade formed by other hystrignathids: two species of Longior Travassos & Kloss, 1958 and Hystrignathus sp.